Bibliometric Analysis on Recent Advances and Development of Microcontroller Application in The Postharvest System - Redika Ardi Kusuma; Rudiati Evi Masithoh (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2023)
Postharvest is a vital stage in agricultural production which is prone to causing losses due to improper implementation. Using a microcontroller that allows automation and increased precision in the postharvest process will likely reduce costs and potential losses. This research conducted a bibliometric study on applying microcontrollers in postharvest systems in Scopus-indexed publications from 2003 to 2022. The aim was to reveal microcontroller developments, evaluate current research topics, and discuss future challenges facing microcontroller applications in postharvest systems. First, this paper presents a bibliometric review of the role of microcontrollers in postharvest. Second, co-citation, coupling, and cluster analysis methods were used to analyze collaboration networks, and VOSviewer was used to visualize these networks. Third, Biblioshiny was used to analyze thematic trends of microcontroller applications. Finally, the paper discusses the challenges of using microcontrollers and provides suggestions for overcoming them. The results show that institutions from China and Italy lead research production in this field, with globally popular studies focusing primarily on fruit, digital storage, moisture determination, and cost. In addition, the thematic evolution of keywords indicating response time, cost, and design reliability issues have become basic and emerging topics in microcontroller application research for postharvest systems in recent years.